The vector of Pineapple Mealybug Wilt-associated Virus (PMWaV) in Sipahutar pineapples in North Tapanuli, Indonesia - LISNAWITA LISNAWITA; AHMAD RAFIQI TANTAWI; MARYANI CYCCU TOBING; ARTHA JUNITA HUTAHAYAN; WISMAROH SANNIWATI SARAGIH; DEWI SARTIAMI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Lisnawita, Tantawi AR, Tobing MC, Hutahayan AJ, Saragih WS, Sartiami D. 2023. The vector of Pineapple Mealybug Wilt-associated Virus (PMWaV) in Sipahutar pineapples in North Tapanuli, Indonesia. Biodiversitas 24: 4052-4059. The Pineapple Mealybug Wilt-associated Virus (PMWaV) disease is one of the most important diseases in pineapples. It Is widely spread in almost all pineapple plantations, including those in North Tapanuli District, North Sumatra Province, Indonesia. Currently, there is still little information on the PMWaV disease and the species of mealybug found in Sipahutar pineapples in the North Tapanuli District. This research aims to identify mealybugs as the vectors that carry the virus that causes PMWaV disease in Sipahutar pineapples. Mealybug samples were taken from 12 villages in four sub-districts in the center of Sipahutar pineapples plantations in the North Tapanuli District. The four sub-districts were Sipahutar Sub-district from Siabal Abal IV Village, Sabungan Nihuta I Village, and Sabungan Nihuta II Village; Siborongborong Sub-district from Bahal Batu I Village, Bahal Batu II Village, and Lobu Siregar Village; Tarutung Sub-district from Parbaju Tonga Village, Jambur Nauli Village, and Sihujur Village; Pangaribuan Sub-district from Pansurnatolu Village, Sigotom Village, and Rahut Bosi Village. Samples were identified morphologically and molecularly. The results of the identification using both methods showed that the mealybugs found on Sipahutar pineapples with PMWaV symptoms from the 12 villages were Dysmicoccus brevipes species.